Pengaruh Modal Kerja Terhadap Tingkat Profitabilitas PT. BFI Finance Indonesia Tbk. - Widadi, Budi; Indrawati, Iin Dyah (LPPM Universitas Harapan Bangsa, 2023)
One of the company’s goals is to get as much profit as possible. Profit or profit is an important means of maintaining the profitability of a business. The higher the expected profit, the better the company can survive, grow and develop and face competition. The purpose of this study was to determine the effect of working capital and operating efficiency on the level of profitability of PT. BFI Finance Indonesia Tbk. This study uses quantitative data types using linear data analysis, with the hypothesis that working capital affect profitability and operational efficiency affects the profitability of PT. BFI Finance Indonesia Tbk